Epidemiology and Clinical Outcomes of COVID-19 Patients in Northwestern China Who Had a History of Exposure in Wuhan City: Departure Time-Originated Pinpoint Surveillance - Zhang, Qingqing; Zhu, Jianfei; Jia, Chenghui; Xu, Shuonan; Jiang, Tao; Wang, Shengyu (Frontiers in Medicine, 2021)
Background: Most coronavirus disease 2019 (COVID-19) patients cannot provide a clear exposure time; therefore, this study was designed to predict the progression of COVID-19 by using the definite departure time from Wuhan. Methods: In this retrospective study, all cases were selected from Northwestern China, which has the lowest population density. As our study endpoints, the incubation period was defined as the date of departure from Wuhan City to the date of symptom onset; we defined the confirmed time as the interval from symptom onset to positive results (samples from the respiratory tract). Both of them were estimated by fitting a Weibull distribution on the departure date and symptom onset. The difference among the variables were analyzed. Results: A total of 139 patients were ultimately enrolled, and approximately 10.1% patients (14 patients) had no symptoms during their disease course. We estimated the median incubation period to be 4.0 days (interquartile intervals, 2.0 to 8.0), and the 95th percentile of the distribution was 15.0 days. Moreover, approximately 5.6% patients (7 patients) experienced symptoms two weeks after leaving. Furthermore, the estimation median interval from symptom onset to final diagnosis was 4.0 days (interquartile intervals, 2.0 to 6.0), and the 95th percentile of the distribution was 12.0 days. Finally, the median hospitalization time was 16.0 days, ranging from 3.0 days to 45.0 days. Univariate analysis showed that age (P=0.021) and severity status (P=0.001) were correlated significantly with hospitalization time. Conclusions: We provide evidence that departure time can be used to estimate the incubation and confirmed times of patients infected with 2019-nCoV when they leave an epidemic area.